Pelatihan Penanganan Kedaruratan Tersedak Pada Masyarakat Awam Di Kelurahan Ciangsana - Christian Soesilo; Diani Nazma; Antin Trilaksmi; Karlina Mahardieni; Noviani Prasetyaningsih (CV. Multi Kreasi Media, 2023)
Choking is a condition where there is a foreign object block somewhere between upper respiratory tract and trachea. The blockage can be total or partial. Blockage in the respiratory tract will result in a decrease in oxygen entering the lungs. This will disrupt cellular oxygenation levels, leading to death. This Community Service activity is aimed at providing additional knowledge about the emergency of choking and its treatment. It is hoped that the community can treat choking incidents as quickly as possible or refer to health centers immediately to reduce morbidity and mortality rates. The activity took place at Trisakti Nagrak campus, Ciangsana village, Gunung Putri sub-district, Bogor, on December 3, 2023. This session was conducted through presentation, watching video, simulation and hands on mannequins, and ended with a question and answer session. Participants were given pre-test questions before session to assess the basic knowledge among participants.